Roflumilast: Review of Phosphodiesterase-4 Inhibitor as Asthma Therapy - Rafina Syfridiana; Fauna Herawati (Universitas Nahdlatul Ulama Surabaya, 2021)
Asthma is a heterogeneous disease characterized by chronic inflammation of the airways induced reversible obstruction resulting in mortality and morbidity. Roflumilast is a second-generation selective inhibitor of phosphodiesterase-4 targeting PDE type 4 isoenzymes, disturbing the breakdown of cyclic AMP (cAMP) and reducing inflammation. However, it has not been recommended for asthma patients because of insufficient evidence from trial results. The search was carried out using the PUBMED online database from 2011 to May 2021. The keywords used in this study were